الحماية القانونية للأشخاص الطبيعيين فيما يتعلق بمعالجة البيانات الشخصية وتداولها: دراسة فى ضوء اللائحة التنظيمية رقم 2016/679 الصادرة عن البرلمان الأوروبى - طه، علاء عيد (جامعة الملك سعود - كلية الحقوق والعلوم السياسية, 2020)
فرضت التطورات المتسارعة في مجال تقنية المعلومات قيام المشرع الأوروبي بإصدار تنظيم جديد لحماية الأشخاص الطبيعيين فيما يتعلق بمعالجة بياناتهم الشخصية وتداولها. فقام بوضع العديد من المبادئ الحاكمة لعملية المعالجة والضوابط على حرية حركة البيانات الشخصية وتداولها. ويجب النظر إلى الحق في حماية البيانات الشخصية على أنه ليس حقا مطلقا، بل ينبغي النظر إليه فيما يخدم المجتمع في كافة المجالات الاجتماعية، والاقتصادية، والأمنية... إلخ وفق ضوابط محددة. لذا اتجه المشرع الأوروبي نحو إيجاد إطار قوي لحماية البيانات مع السماح بتوظيف معالجة البيانات في دعم الاقتصاد الرقمي والسوق الداخلية. وقد حافظ المشرع الأوروبي في هذا التنظيم الجديد لحماية البيانات الشخصية على الحقوق الأساسية للأفراد، وتقيد بالمبادئ المعترف بها في الميثاق الأوروبي والمعاهدات الدولية، لاسيما احترام الحياة الخاصة، والأسرية، والاتصالات، وحرية التعبير، والمحاكمة العادلة، وإدارة الأعمال التجارية، والتنوع الثقافي والديني واللغوي. إضافة لما سبق، فقد حرص المشرع الأوروبي في التنظيم الجديد لحماية البيانات الشخصية على معالجة العديد من الإشكالات القانونية التي تنتج عن عملية معالجة البيانات أبرزها الحق في أمن البيانات وسريتها، ومعالجة البيانات في سياق العمل، والحق في النسيان الرقمي، ومعالجة البيانات الشخصية لأغراض إعلانية، أو لأغراض البحث العلمي أو التاريخي أو لأغراض إحصائية... إلخ.
Rapid developments in the field of information technology have forced the European legislator to issue a new regulation to protect people in the processing and handling of their personal data. The European legislator developed several principles governing the processing of data and the controlling of the free movement. The right to the protection of personal data must be seen as not an absolute right, but should be seen in the service of society in all social, economic, security spheres, etc. according to specific controls. Thus, the European legislator has tended to create a strong data protection framework while allowing the use of data processing to support the digital economy and the domestic market. The European legislator, in the new data protection regulation, has preserved the fundamental rights of individuals and has applied the principles recognized in the European Charter and international treaties, in particular the respect for private and family life, communications, freedom of expression, fair trial and administration business, cultural, religious and linguistic diversity. In addition to the above, the European legislator, in the new European Regulation for the protection of personal data, has addressed many of the legal forms that resulted from the process of data processing, most notably the right to data security and confidentiality, data processing in the context of work, and the right to digital forgetting, processing of personal data for advertising purposes, for purposes of scientific or historical research or for statistical purposes, etc.
Keywords: الحماية القانونية -- البرلمان الأوروبى -- البيانات الشخصية